Pengaruh ROA, CR dan DER Terhadap Nilai Perusahaan pada Sektor - Setiya Kumala Dewi; Hari Setiono; Muhammad Bahril Ilmidavviq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research is intended to evaluate the impact of ROA, CR and DER on company value (PBV) during the 2021–2023 period, focusing on technology companies listed on the IDX. The target sampling method was used to select samples for research. SPSS version 22 was used to carry out multiple regression data analysis. The research results state that DER has a positive impact on company value. Although, ROA and CR do not have a significant impact. The F test results also confirm that ROA, CR, and DER influence company value simultaneously. This study shows that, with an R-squared (R2) value of 89.5%, the 89.5% difference in company value can be explained by a combination of Return on assets (ROA).